Distributions of nitrogen and phosphorus in ice-covered water systems and comprehensive evaluation of water quality in reservoirs during the freezing period. Issue 3 (16th March 2022) - Hu, Suduan; Wang, Tiangxiang; Xu, Shiguo; Ma, Lingxiao; Sun, Xinguo; Wang, Tianzi
ABSTRACT: The distributions of nitrogen and phosphorus and the comprehensive water quality of reservoirs during freezing periods constitute weaknesses in water quality management strategies during certain periods. In this paper, ice and water samples of a typical reservoir, Biliuhe reservoir, were collected and analysed, and the comprehensive water quality was evaluated by the variable fuzzy recognition method. The results showed that the effect of 'salt exclusion' during ice formation was obvious, with exclusion factors of 10.54 and 1.26 for total nitrogen (TN) and total phosphorus (TP), respectively. The evaluation results showed that the comprehensive water quality of the water column and ice were 2.68 and 1.44, respectively, during the freezing period. When considering the effect of salt exclusion, the TN and TP contents in the surface water of the reservoir were 3.15 and 2.62 times the previous contents, respectively, and the evaluation results showed that the surface water quality decreased by 5%. The effect of salt exclusion during ice formation in winter mainly occurred in the top layer of the water column under ice in the deep reservoir. It is necessary to further study the influence of reservoir sediments on water quality in ice-covered water systems.